Relations of Emir Timur with Europe before and after the Battle of Ankara » - Kirpik Güray (Золотоордынское обозрение)
The article examines the views of European historians on the relations between Amir Timur (Tamerlane) and Europe before and after the Battle of Ankara (1402). The author pays particular attention to the diplomatic correspondence, papal relations with European monarchies, recordings made during the hostilities, and diplomatic missions. The article also highlights the changing image of Amir Timur among Europeans. The most significant changes that took place after the Battle of Ankara are reflected in the official correspondence of the European kings, the Papacy, and the Byzantine emperors. On the one hand, the battle itself was provoked by European and Byzantine rulers. On the other hand, it was a direct consequence of the growth of contradictions between the rulers of Anatolia and Central Asia. At the same time, the author considers that Europe and Byzantium, belonged to a completely different cultures, striving to achieve various political goals, while the Ottoman Sultan Bayezid I and Emir Timur, being exclusively Turkic rulers, sought to achieve the same goals using similar methods of political struggle.